ChemInform Abstract: BF3·Et2O‐Promoted Cleavage of the C(sp)—C(sp2) Bond of 2‐Propynolphenols/Anilines: Route to C2‐Alkenylated Benzoxazoles and Benzimidazoles. Issue 28 (July 2015) - Song, Xian‐Rong; Qiu, Yi‐Feng; Song, Bo; Hao, Xin‐Hua; Han, Ya‐Ping; Gao, Pin; Liu, Xue‐Yuan; Liang, Yong‐Min
Abstract Propargylic alcohols of type (I) and (V) having an ortho‐hydroxyphenyl substituent undergo a BF3‐promoted reaction with azide to yield 2‐alkylated benzoxazoles (II) and (VI).